Lucas Davenport : Gathering Prey - Book 25 - Sandford, John 1944 February 23- (New York G. P. Putnam's Sons, 2015)
"The extraordinary new Lucas Davenport thriller from #1 New York Times-bestselling author and Pulitzer Prize-winner John Sandford. They call them Travelers. They move from city to city, panhandling, committing no crimes-they just like to stay on the move. And now somebody is killing them. Lucas Davenport's adopted daughter, Letty, is home from college when she gets a phone call from a woman Traveler she'd befriended in San Francisco. The woman thinks somebody's killing her friends, she's afraid she knows who it is, and now her male companion has gone missing. She's hiding out in North Dakota, and she doesn't know what to do. Letty tells Lucas she's going to get her, and, though he suspects Letty's getting played, he volunteers to go with her. When he hears the woman's story, though, he begins to think there's something in it. Little does he know. In the days to come, he will embark upon an odyssey through a subculture unlike any he has ever seen, a trip that will not only put the two of them in danger-but just may change the course of his life"--
Kirkus Reviews
Publishers Weekly
Library Journal Prepub Alert
Adult
Adult
Keywords: Davenport, Lucas (Fictitious character) -- Fiction; Detectives -- Fiction -- Minneapolis (Minn.); Homicide -- Fiction; Criminal investigation -- Fiction; Mystery fiction